Clinical and epidemiological profile of children with congenital toxoplasmosis in a reference institute of perinatology (Research, Society and Development, 2021)
Objective: To analyze congenital toxoplasmosis in children followed at the Social Perinatology Institute of the Dona Evangelina Rosa Maternity Hospital. Methodology: This was a descriptive, quantitative cross-sectional documentary research study. The study included 85 newborns who were exposed to toxoplasmosis during pregnancy, born between January 2018 and December 2021. Data collection was performed using the “Congenital Toxoplasmosis Reporting/Investigation Sheets of the Notifiable Diseases System ”. Results: It was found that most pregnant women were aged between 20 and 29 years at the time of diagnosis. The gestational age at which most mothers were diagnosed was also observed, diagnosis occurred during the range of 37 weeks to 40 weeks and 6 days of gestation. In addition, approximately 56% of the children did not present clinical alterations. Among symptomatic children, the most common alterations were retinochoroiditis, prematurity, jaundice, hydrocephalus and ascites. The results showed that about 53% of the children used the combination of Sulfadiazine + Pyrimethamine + Folinic Acid. Conclusion: It was possible to trace the epidemiological profile of pregnant women diagnosed with toxoplasmosis, as well as the clinical manifestations, treatment and evolution of children with congenital toxoplasmosis were evaluated.